Pengembangan Middleware Web of Things sebagai Antarmuka Akses Batch dan Stream Perangkat Sensor berbasis Protokol Bluetooth Low Energy - Satria Adhi Kharisma; Adhitya Bhawiyuga; Eko Sakti Pramukantoro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Healthcare is one of the interesting fields in the application of IoT. However, the devices used in the implementation of IoT-based healthcare are very heterogeneous, this is a challenge for application developers to overcome the different communication mechanisms in sensing devices. In addition, the IoT application requires batch and stream data processing. Based on these challenges and requirements, the authors develop middleware to overcome these challenges. Middleware consists of three components it is sensor-to-cloud gateway components, messaging services, and data access interfaces. After implementation we perform device management, sensor-to-cloud gateway, messaging service, batch interface and stream interface test. Device management testing shows that the gateway component is able to manage sensor devices using BLE. Sensor-to-cloud gateway testing shows the ability of the gateway to forward sensor device data to the cloud. The messaging service test shows the ability of middleware to store messages in a database and facilitate the access stream interface. In batch and stream testing it can be seen that middleware can provide data for client users in batch and stream.